P134 Methacholine challenge to demonstrate therapeutic equivalence of terbutaline via different turbuhaler devices in patients with mild to moderate asthma: appraisal of a phase iii, four-way crossover design. (15th November 2016) - Bjermer, L; Gauvreau, G; Postma, D; O'Byrne, P; Berge, M van den; Boulet, L-P; Beckman, O; Persson, T; Roman, J; Carlholm, M; Schutzer, K-M; Eckerwall, G
Abstract : Background/objective: To demonstrate therapeutic equivalence of terbutaline via two different Turbuhaler® devices by evaluating its protective effect against methacholine-induced bronchoconstriction in patients with stable asthma. Methods: In this double-blind, double-dummy, multicentre, single-dose, 4-way crossover study, patients with stable, mild-to-moderate asthma (FEV1 ≥ 80% predicted normal) were randomised to 0.5 or 1.5 mg terbutaline via either Turbuhaler® M3 or M2 followed by a methacholine challenge test. Primary outcome variable: concentration of methacholine causing a 20% drop in FEV1 (PC20). Patients had to have a PC20 methacholine < 8 mg/mL, reproducible after 2 weeks, and a stable baseline FEV1 at all visits (90–110% of enrolment value). Results: 60 patients were randomised to treatment and completed the study. There was a clear dose–response for both devices. The within-device ratios (1.5 mg: 0.5 mg) were 1.79 and 1.87 for Turbuhaler M3 and M2, respectively (both p < 0.001). The between-devices ratio (M3:M2) was 0.92 (95% CI: 0.75–1.13) for 0.5mg and 0.88 (95% CI 0.72–1.08) for 1.5 mg. Both CIs lie inside the interval (0.67–1.50), which was the pre-specified condition for equivalent effect. Conclusions: Bronchoprotection with PC20 as the outcome measure in a standardised methacholine challenge model proved to be a useful design to show therapeutic equivalence between devices in patients with mild to moderate asthma. This model provides robust reproducible data, involves smaller patient numbers with fewer dropouts resulting in reduced costs versus a conventional efficacy study.